KIAS LANGUAGE ON FAMILY WELFARE PROGRAMME IN SANGKEP OF CREATIVE ECONOMIC EMPOWERMENT AS IMPACT OF MOUNT AGUNG ERUPTION - Tari, Nirmala; Majuarsa, I Wayan; Dwiyanti, Ni Made Christine (International Conference on Cultural Studies, 2019)
The languages spoken by a member of the Family Welfare Programme appearance are very rich languages, style and word choice used in the role of each statement when Sangkep . The primary purpose of Sangkep , besides, to discuss the creative idea to empower member. It is also to convey the values of struggling life as well as to maintain the economic impact of mount Agung eruption. Member uses several special languages to provide emphasis as well as invitations to others. Not all types of kias language can be found in this study. The kias language is discussed in this study, they are simile, metaphor, personification, eponyms, cynicism, sarcasm, satire. Sangkep as media to hold the public idea, also convey the contents of togetherness life to the next generation directly. The languages are spoken in sangkep show invitation, so as to provide an encouragement to solve every problem. Therefore, member more often uses the kias language in conveying the information to be conveyed to others to reach in solving the problems.